2012
DOI: 10.1007/s10948-012-1862-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Anisotropic Fluctuation Diamagnetism Around the Superconducting Transition of Ba1−x K x Fe2As2 Single Crystals in the Finite-Field (or Prange) Regime

Abstract: The magnetization around the superconducting transition was recently measured in a high-quality Ba 1-x K x Fe 2 As 2 single crystal with magnetic fields applied along and transverse to the crystal Felayers [J. Mosqueira et al., Phys. Rev. B 83, 094519 (2011)]. Here we extend this study to the finite field (or Prange) regime, in which the magnetic susceptibility is expected to be strongly dependent on the applied magnetic field. These measurements are analyzed in the framework of the threedimensional anisotropi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…The absence of the scaling suggests that a different fluctuating mechanism has to be found. We note that our data are not in disagreement with recent results on ironpnictides [34], since we are dealing with a weak field region. On the contrary at stronger fields, the 3D scaling is recovered, as also shown in figure 7.…”
Section: Discussion and Interpretation Of The Resultssupporting
confidence: 60%
“…The absence of the scaling suggests that a different fluctuating mechanism has to be found. We note that our data are not in disagreement with recent results on ironpnictides [34], since we are dealing with a weak field region. On the contrary at stronger fields, the 3D scaling is recovered, as also shown in figure 7.…”
Section: Discussion and Interpretation Of The Resultssupporting
confidence: 60%
“…One of them is their dimensionality. In these materials the transverse coherence length amplitude ξ c (0) is close to the Fe layers periodicity length, s. Thus, depending on the particular compound studied, some works report a two-dimensional (2D) behavior [3,10,20] similar to the one found in highly anisotropic HTSC, [24] while others find three-dimensional (3D) characteristics, [4,5,6,7,11,12,14,15,16,19,21,22,23] or even a 3D-2D transition [8,13,18] when increasing the temperature above T c (as in optimally-doped YBa 2 Cu 3 O 7−δ ) [24]. ‡ But it was recently reported that the fluctuation electrical conductivity above T c of clean LiFeAs crystals seemingly follows a well defined 2D behavior (in both the amplitude and the reducedtemperature dependence), despite that for this compound ξ c (0) ≈ 1.6 nm is much larger than the Fe-layers periodicity length (s = 0.636 nm).…”
Section: Introductionmentioning
confidence: 83%
“…[3] In addition to their intrinsic interest, the superconducting fluctuation effects are a very useful tool to characterize the nature of a superconducting transition and to obtain material parameters, [2] so that different works have already addressed their study in FeSC through observables like the magnetization, specific heat or the electric conductivity. [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23] However, some fundamental aspects of the phenomenology of the fluctuation effects in these materials are still debated. One of them is their dimensionality.…”
Section: Introductionmentioning
confidence: 99%
“…The fluctuation effects have been recently used in a number of works to characterize the superconducting properties of Fe-based superconductors, through observables like the electrical conductivity, magnetization, or specific heat [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Nowadays, the properties of these materials at the optimal doping were extensively studied and are already rather well understood.…”
Section: Introductionmentioning
confidence: 99%